2010
DOI: 10.1111/j.1540-8159.2009.02623.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation of Typical Atrioventricular Nodal Reentrant Tachycardia in Children: Six Years’ Experience and Follow-Up in a Single Center

Abstract: Acute and long-term results demonstrate that cryoablation of AVNRT can be considered a safe and effective procedure in pediatric patients. (PACE 2010; 475-481).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 27 publications
0
45
0
4
Order By: Relevance
“…6,7,12 Providing data on a significantly longer follow-up, we found a substantial portion of late recurrences even >5 years after ablation. As previous studies reported on a follow-up of 2 to 3 years post ablation, 2,5-7 long-term freedom from AVNRT >3 years after ablation might have been systematically overestimated.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…6,7,12 Providing data on a significantly longer follow-up, we found a substantial portion of late recurrences even >5 years after ablation. As previous studies reported on a follow-up of 2 to 3 years post ablation, 2,5-7 long-term freedom from AVNRT >3 years after ablation might have been systematically overestimated.…”
Section: Discussionmentioning
confidence: 89%
“…3 In children and adolescents, data from the pediatric radiofrequency catheter ablation registry acquired more than a decade ago reported a significant number of recurrences with 71% freedom from AVNRT 3 years post ablation. 4 However, recent follow-up studies of pediatric patients after AVNRT ablation reported freedom from AVNRT between 84% and 100% with radiofrequency 2,5 and between 78% and 93% with cryoenergy, [6][7][8] respectively. These studies on a limited number of pediatric patients analyzed data on the follow-up of 1 to 3 years post ablation.…”
mentioning
confidence: 99%
“…In particular, no relapses were observed for patients younger than 21 years: this is of special interest, as in this subset of patients cryotherapy is usually preferred over RF because of its lower risk of permanent side effects. 5,6 As far as we know, this is the first investigation in which an age-related effect on ablation outcome is described for patients with AVNRT undergoing CA, as previous studies were performed in patients treated by RF. 16,17 Hoffmann et al 16 reporting the results from the German Ablation Registry found no differences in recurrence rate across different classes of age (o50, 50-75, and 475 years); however, in that population, only 2.3% of patients were treated with CA and no subgroup analysis was reported according to the kind of energy delivered.…”
Section: Discussionmentioning
confidence: 94%
“…This makes CA particularly useful in high-risk cases, such as ablation of arrhythmic substrates localized in the proximity of the His bundle or of the compact atrioventricular (AV) node, and the preferred approach for ablation in pediatric patients at some centers. 5,6 With regard to short-and long-term tachycardia eradication, most series favor RF ablation, 7 but others have suggested comparable efficacy with either techniques 2 ; furthermore, some groups could demonstrate a significant increase in the procedural success rate with increasing experience, 6 despite initial less satisfactory results. 8 The purpose of our study was to assess which factors may affect the acute and long-term CA efficacy in the treatment of typical (slow-fast) AVNRT.…”
Section: Introductionmentioning
confidence: 96%
“…Отсутствие нарушений АВ проведения при криопробе не гарантирует того, что они не возникнут в ходе абляции. При этом, криовоз действие признано более безопасным, что, не сомненно, важно у определенных групп паци ентов (например -у детей) [12,13].…”
Section: Discussionunclassified